2008
DOI: 10.3164/jcbn.2008007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Medium-Chain Triacylglycerol on Serum Albumin and Nitrogen Balance in Malnourished Rats

Abstract: Summary The present study was examined the therapeutic effect of medium-chain triacylglycerol (MCT) in protein-energy malnutrition (PEM). Wistar rats were fed low protein diet containing 70 g/kg of long-chain triacylglycerol (LCT) or MCT for 31 days. The serum albumin concentration in rats fed MCT diet (2.88 ± 0.04 g/dl) were significantly higher compared with those fed LCT diet (2.72 ± 0.04 g/dl) at day 31. Nitrogen balance was higher in rats fed MCT diet (54.1 ± 2.3 mg/day) compared with those fed LCT diet (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
(25 reference statements)
1
13
0
1
Order By: Relevance
“…When serum albumin decreased by 1 g/L, the odds of being classified as malnourished increased 1.1-fold (25); thus, serum albumin is a marker of nutrition status (26). The present study showed that dietary MCT improved plasma albumin concentration compared with LCT (Table 3), similar to the results of a previous study (5,6). In addition, the liver albumin level was higher in the MCT-fed group than in the LCT-fed group (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…When serum albumin decreased by 1 g/L, the odds of being classified as malnourished increased 1.1-fold (25); thus, serum albumin is a marker of nutrition status (26). The present study showed that dietary MCT improved plasma albumin concentration compared with LCT (Table 3), similar to the results of a previous study (5,6). In addition, the liver albumin level was higher in the MCT-fed group than in the LCT-fed group (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies showed that dietary MCT improved serum albumin concentration in malnourished rats (5,6) and in elderly people with PEM status (4). However, the mechanism for this effect of dietary MCT was not clarified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The urinary albumin excretion rate was calculated from urinary albumin, measured using nephelometry (antibody binding) technique 13,15 . Urinary protein was measured using a commercial kit 16 . Insulin levels were assessed using a commercial ELISA kit for rat insulin by sandwich type immunoassay using monoclonal antibody specific for rat insulin 17 .…”
Section: Methodsmentioning
confidence: 99%